2018
DOI: 10.3390/molecules23081981
|View full text |Cite
|
Sign up to set email alerts
|

New 2-Oxoindolin Phosphonates as Novel Agents to Treat Cancer: A Green Synthesis and Molecular Modeling

Abstract: The work reports the facile synthesis of novel α-aminophosphonate derivatives coupled with indole-2,3-dione moieties, namely the diethyl(substituted phenyl/heteroaryl)(2-(2-oxoindolin-3-ylidene)hydrazinyl)methylphosphonates derivatives 4(a–n). One-pot three component Kabachnik-Fields reactions were used to synthesize these derivatives. The reaction was carried out at room temperature by stirring in presence of ceric ammonium nitrate (CAN) as a green catalyst. The structures of the synthesized compounds were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Tumor cells are characterized by, e.g., an unlimited potential for proliferation [ 26 ]; hence, restriction of tumor cell proliferation via cell cycle arrest and/or apoptosis induction is an expected feature of new compounds with anti-cancer potential. It is reported that OP compounds, including those based on α-aminophosphonate scaffolds, exhibit anti-proliferative activity towards various types of cancer, e.g., leukemia, melanoma, colon cancer, hepatoma, breast cancer, lung cancer, and neuroblastoma [ 3 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. According to these reports, the growth inhibitory effect of αAPs was associated with apoptosis induction and cell cycle arrest mostly at the G 2 phase.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells are characterized by, e.g., an unlimited potential for proliferation [ 26 ]; hence, restriction of tumor cell proliferation via cell cycle arrest and/or apoptosis induction is an expected feature of new compounds with anti-cancer potential. It is reported that OP compounds, including those based on α-aminophosphonate scaffolds, exhibit anti-proliferative activity towards various types of cancer, e.g., leukemia, melanoma, colon cancer, hepatoma, breast cancer, lung cancer, and neuroblastoma [ 3 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. According to these reports, the growth inhibitory effect of αAPs was associated with apoptosis induction and cell cycle arrest mostly at the G 2 phase.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the isatin hybrids mentioned above, some other hybrids also showed certain anticancer activity, such as hybrid 61a (GI 50 : 0.75–28.39 μM, SRB assay) displayed broad‐spectrum activity against a panel of cancer cell lines derived from nine different cancer types: leukemia, melanoma, lung, colon, CNS, ovarian, renal, prostate, and breast cancers. [ 122–128 ] However, the majority of them were not superior to the references and still need to be modified.…”
Section: Isatin–coumarin Hybridsmentioning
confidence: 99%
“… 9 Additionally, non-proteogenic α-hydrazino phosphonic acid derivatives, in which intramolecular H-bonds (hydrazino turns) 10 might modify their biological activities, have emerged as promising targets in medicinal chemistry. In particular, α-hydrazinophosphonate oxadiazoles I, 11 isatin derivatives II 12 and hydrazide III 4 a have been reported to exhibit promising activities against different types of cancer (I and II) and antimicrobial activity against K. Pneumonia (III) ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%